Activities of the committee for the extermination of locusts of the Tersk regional government in the territory of Nalchik district in the last quarter of the 19th century - Elena A. Anishchenko (Кавказология, 2025)
The article defines the role of the Committee for the Extermination of Locusts in the Tersk region, one of the structures of the economic part of the Tersk regional government in the last quarter of the 19th century. During this period, one of the ways to include the population of the Central Caucasus in the socio-economic space of the Russian Empire was to address issues of improving agricultural efficiency through the introduction of new agricultural practices, including improving measures to control insect pests such as ranching. The article examines the functions of the Locust Extermination Committee and the mechanisms for its activities to develop and implement measures to control locusts using the example of the Nalchik district. The financial aspects of implementing a pest protection system for crops and crops are analyzed. The conclusion is made about the synthesis of a scientific and research approach in the study of natural factors that favored the emergence and spread of a locust population, such as monitoring its life cycle from egg laying to the appearance of adults, studying the natural and climatic conditions of specific localities that increased the likelihood of locust spread, and practical activities to develop a com-a set of measures for the extermination of locusts, ways of their implementation, as well as their systematic introduction into the daily agricultural life of the population.